Microseismicity in the period 07/2007-12/2007 at Louisville seismic gap: SEISAN waveform files - Yingchen Liu; Dietrich Lange; Ingo Grevemeyer (PANGAEA, 2024)
From July to December of 2007 a seismic network of ocean-bottom-seismometers was deployed in the south of Louisville seismic gap and its southern adjacent area. This dataset provides waveform event files of the largest local earthquakes detected in continuous waveform data, with magnitudes between 2.0 and 6.9. The zip-file includes waveform data and two Nordic files (one for local events and another for regional events) and a station file with station coordinates in SEISAN format. All data in the zipped file can be processed and used with the SEISAN seismology software. The stations were installed in 2007 using the German research vessel SONNNE for deployment (SO194) and recovery (SO195).